An educational software for measurements demonstrations and data logging with Arduino boards - Perea Martins, J. E.M. [UNESP] (IOP Publishing, 2020)
This work presents an educational freeware software that operates as a data logger and a large display to allow a satisfactory viewing of the numerical information, even by students far from the experiment, and therefore it is a tool designed to help experimentations and demonstrations based on Arduino boards in educational physics laboratories.
Keywords: data logger; display; experiment demonstration